On the numerical approximation of first-order Hamilton-Jacobi equations - Abgrall, Rémi; Perrier, Vincent (Zielona Góra: Uniwersytet Zielonogórski)
Some methods for the numerical approximation of time-dependent and steady first-order Hamilton-Jacobi equations are reviewed. Most of the discussion focuses on conformal triangular-type meshes, but we show how to extend this to the most general meshes. We review some first-order monotone schemes and also high-order ones specially dedicated to steady problems.
Keywords: approximation of Hamilton-Jacobi equations; viscous solution; Cauchy-Dirichlet problem; triangular mesh